Clinical and cytogenetic characteristics of patients with Triple X syndrome: Experience from a tertiary center - Ürel Demir, Gizem; Açıkgöz, Nazlı Büşra; Utine, Gülen Eda; Şimşek Kiper, Pelin Özlem (Acta Medica, 2026)
Background: Triple X syndrome is the most common sex chromosome aneuploidy in females; however, due to the subtlety of clinical findings, only a small proportion of affected individuals are diagnosed. This study presents the demographic, clinical, and cytogenetic characteristics of patients with Triple X syndrome followed at a single center. Methods: We retrospectively reviewed the medical records of patients diagnosed with Triple X syndrome at our department between 2008 and 2025. Demographic characteristics, clinical findings including anthropometric measurements, dysmorphic features, associated anomalies, endocrine and neurodevelopmental findings, and cytogenetic results were analyzed. Results: The study included a total of 20 patients diagnosed with Triple X syndrome, 13 of whom (65%) had a non-mosaic 47,XXX karyotype and 7 (35%) had mosaic chromosomal abnormalities. Four patients received a prenatal diagnosis, four were diagnosed in adulthood, and the remaining patients were diagnosed during childhood. Dysmorphic features; neurodevelopmental problems such as developmental delay, intellectual disability, and attention-deficit/ hyperactivity disorder; as well as cardiac defects and endocrine disorders were the main characteristics observed in the patients. Conclusion: Triple X syndrome is a relatively common chromosomal disorder, which should be considered in patients who experience congenital anomalies, neurodevelopmental abnormalities, and reproductive problems. Variable and subtle findings should be carefully considered, bearing in mind that mosaic cases may present with diverse and overlapping phenotypes.